The CORDEX-CORE EXP-I Initiative: Description and Highlight Results from the Initial Analysis - Giorgi, Filippo; Coppola, Erika; Jacob, Daniela; Teichmann, Claas; Omar, Sabina Abba; Ashfaq, Moetasim; Ban, Nikolina; Bülow, Katharina; Bukovsky, Melissa; Buntemeyer, Lars; Cavazos, Tereza; Ciarlo, James; et al. (American Meteorological Society, 2022)
We describe the first effort within the Coordinated Regional Climate Downscaling Experiment-Coordinated Output for Regional Evaluation, or CORDEX-CORE EXP-I. It consists of a set of twenty-first-century projections with two regional climate models (RCMs) downscaling three global climate model (GCM) simulations from the CMIP5 program, for two greenhouse gas concentration pathways (RCP8.5 and RCP2.6), over nine CORDEX domains at ~25-km grid spacing. Illustrative examples from the initial analysis of this ensemble are presented, covering a wide range of topics, such as added value of RCM nesting, extreme indices, tropical and extratropical storms, monsoons, ENSO, severe storm environments, emergence of change signals, and energy production. They show that the CORDEX-CORE EXP-I ensemble can provide downscaled information of unprecedented comprehensiveness to increase understanding of processes relevant for regional climate change and impacts, and to assess the added value of RCMs. The CORDEX-CORE EXP-I dataset, which will be incrementally augmented with new simulations, is intended to be a public resource available to the scientific and end-user communities for application to process studies, impacts on different socioeconomic sectors, and climate service activities. The future of the CORDEX-CORE initiative is also discussed.
Keywords: Climate change; Climate models; Regional effects; Regional models